Reduced graphene oxide composite with oxidizable manganese/cobalt mixed oxide for p-cresol oxidation by using molecular oxygen - Jha, Ajay; Patil, Sagar H.; Solanki, Bhanu P.; Ribeiro, Ana P. C.; Castro, Carlos A. N.; Patil, Kashinath R.; Coronas, Alberto; Rode, Chandrashekhar V. (ChemPlusChem, 2015)
A composite of graphene oxide (GO) with mixed oxide (MnCo) was prepared by using a solvothermal method. During the synthesis, both the reduction of GO and growth of metal oxides took place simultaneously. The as-prepared composite material was highly selective for the liquid-phase oxidation of p-cresol to form p-hydroxybenzaldehyde in 71% yield within 1h. The composite material was characterised by SEM, X-ray photoelectron spectroscopy, high-resolution TEM and cyclic voltammetry (CV). A CV study revealed that the increase in the redox potential of the mixed oxide after being supported on GO, led to its higher activity of the catalyst for the oxidation reaction. The stability of the catalyst under the reaction conditions was studied by its successful reuse in three cycles.
Keywords: cyclic voltammetry; graphene; Oxidation; supported catalysts; transition metals